EVOLUTION DE LA FORME DE L’ETAT CONTENUE DANS LES CONSTITUTIONS DE 1960 ET CELLE DU 18 FEVRIER 2006 TELL QUE MODIFIER ET COMPLETE PAR LOI N° 11/002 DU 20 JANVIER 2011 EN R D C - TSHINKENKA, Evariste NSUMBU (IJRDO - Journal of Social Science and Humanities Research, 2021)
The determination of the form of state is a question which has been the subject of crucial political debate in the political history of African countries in general and of the Democratic Republic of Congo in particular. The Constitution in Africa should be understood as being a governmental tecnique not established with the aim of recognizing the putting of power at the service of the community or of various legal or intellectual fictions which refer to it (the Nation, the Country, the Homeland, the Common good, the general interest) but exercid whith a view to fixing political roles, from the final location of the actors to the relatio ship. From the Independent state of the Congo through the Belgian congo to this day, the Constitution or in particular the form of state applicable to the congolese people. Today, many are those who wonder what is the form of the state for the Democratic Republic of Congo from independence to the present day. By making a historical overview of the form of the state in the various constitutions known to the Democratic Republic of Congo, either from the fundamental law through the constitution of June 24,1964 that the current constitution of february 18, 2006 that the majority of constitutions provide for the unitary form of the state, where as a minority provides for federalism, the form of the state constitution of 1960 and that of February 18, 2006. The constitution is the supreme law of the Democratic Republic of Congo, it is from this fundamental law no law can be contrary to the constitution and there fore can not oppose it or reduce its scope. This document defines the type of company organized in contry. This, since the independence of the Democratic Republic of Congo the form of the state contained in the various constitutions is always unitary even if the other constitutions of federalism, the charcter is always there.